ANALISIS PENERAPAN KREATIVITAS DAN INOVASI DALAM PENGELOLAAN SAMPAH PLASTIK SEBAGAI BASIS KEWIRAUSAHAAN SOSIAL: STUDI KASUS PROGRAM CITARUM REPAIR DI KECAMATAN CIHAMPELAS - Nuryan, Iwan (Media Riset Bisnis & Manajemen, 2025)
The increasingly complex issue of plastic waste in Indonesia demands creative, innovative, and participatory management approaches. The Citarum Repair Program, organized by Greeneration Foundation and its partners, presents a collaborative, technology-based, and community-driven river waste management effort. This study aims to analyze the implementation of creativity and innovation in plastic waste management through the Citarum Repair program, and to evaluate the potential for social entrepreneurship emerging from it. A qualitative descriptive approach was used with a case study method in Cihampelas Subdistrict, West Bandung Regency. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings show that the program adopts creative strategies through educational campaigns and community engagement, and applies technological innovations such as trash booms and conveyors to collect river waste. However, the potential for social entrepreneurship remains underutilized as the program focuses primarily on education and waste retrieval. The study recommends strengthening a social entrepreneurship model through circular economy-based waste management and empowering local communities as environmental-based business actors. These findings contribute to the discourse on plastic waste management through creative-innovative approaches and are relevant to sustainable environmental policy development.